A simple Synthesis of the Debrominated Analogue of Veranamine. (February 2015) - Liang, Dawei; Wang, Yueqiu; Wang, Yanyan; Di, Donghua
A facile synthesis of 4, 5, 5-trimethyl-5, 6-dihydrobenzo[c][2, 7]naphthyridine, the debrominated analogue of the marine alkaloid veranamine, has been achieved in three steps with a 38% overall yield. from the commercially available 2-bromoaniline. The key benzo[c][2, 7]naphthyridine moiety was constructed using a Sonogashira coupling, a tandem Rupe rearrangement–Donnelly–Farrell cyclisation and a Diels–Alder reaction as the key steps. The synthetic strategy allows rapid access to various analogues of veranamine.